KADAR EKSTRAKTIF BATANG POHON JABON PUTIH (Neolamarckia cadamba) DAN JABON MERAH (Neolamarckia macrophyllus) DARI WONOGIRI, JAWA TENGAH - Fatra Valahatul Ihda; Ganis Lukmandaru; Arif Nirsatmanto (Faculty of Forestry Universitas Gadjah Mada, 2023)
Jabon is a fast-growing tree species with two types, white and red. The families or the origin of the mother tree are sources of variation that influence the chemical composition, particularly the extractive properties. This research aimed to determine the chemical properties of the wood and bark of 10-year-old white Jabon (families 23, 11, and 6) and 5-year-old red Jabon (families 75, 85, and 2) planted in a progeny test plot in Wonogiri, Central Java. In the wood portion of white Jabon, family 23 had the highest n-hexane (HEC), methanol (MEC), and hot water (HWEC) soluble extractive contents, as well as total extractive content (TEC) and total flavonoid content (TFC), while family 6 had the highest total phenolic content (TPC). Meanwhile, in red Jabon, family 75 had the highest HEC, HWEC, and TFC, family 2 had the highest MEC and TEC, and family 85 had the highest TPC. In the bark portion, family 11 had the highest HEC, MEC, TEC, and TPC, while family 6 had the highest HWEC and TFC for white Jabon. In red Jabon, family 2 had the highest HEC, family 85 had the highest MEC, HWEC, and TEC, while family 75 had the highest TPC and TFC.